Conferences and combination lectures in the Elizabethan church : Dedham and Bury St Edmunds, 1582-1590 - Collinson, Patrick; Craig, John, 1963-; Usher, Brett, 1946-2013 (Church of England Record Society (Series) ;, 2003)
At the heart of Elizabeth I's reign, a secret conference of clergymen met in and around Dedham, Essex, on a monthly basis in order to discuss matters of local and national interest. Their collected papers, a unique survival from the clandestine world of early English nonconformity, are here printed in full for the first time, together with a hitherto unpublished narrative by the Suffolk minister, Thomas Rogers, which throws a flood of light on similar, if more public, clerical activity in and around Bury St Edmunds, Suffolk, during the same period.